Nature as Guide: Wittgenstein and the Renewal of Moral Theology by David Goodill, OP, The Catholic University of America Press, Washington D.C., 2022, pp. xiii+319, £62.89, hbk - Selman, Francis (New blackfriars, 2024)
Nature as Guide: Wittgenstein and the Renewal of Moral Theology by David Goodill, OP, The Catholic University of America Press, Washington D.C., 2022, pp. xiii+319, £62.89, hbk - Volume 105 Issue 5